Trastuzumab-Related Cardiotoxicity in Early Breast Cancer: A Cohort Study - Bonifazi, Martina (AlphaMed Press, 2013)
BACKGROUND. Concerns have been raised about the cardiac safety profile of trastuzumab for the adjuvant treatment of early stage breast cancer in clinical practice. We assessed trastuzumab-related cardiotoxicity and its predictors in a large cohort of Italian women. METHODS. Through a record linkage between four regional health care databases, we identified the rate of severe cardiac adverse events among women treated with trastuzumab for early breast cancer in Lombardy. The cumulative risk of cardiotoxicity was estimated using the Kaplan-Meier method, and independent predictors were assessed using the Cox model. RESULTS. Of 2,046 trastuzumab users, 53 (2.6%) experienced at least one hospitalization for a cardiac event, and there were two cardiac deaths. The cumulative risk of cardiotoxicity increased up to 2 years after starting treatment, reaching a plateau at 2.8%. The risk was low (0.2%) among young women, whereas the incidence was approximately 10% in women aged ≥70 years, irrespective of cardiovascular risk factors. Age and history of cardiac disease were strong predictors of cardiotoxicity, with a hazard ratio of 11.3 (95% confidence interval [CI]: 3.5–36.6) for women aged ≥70 years as compared with those <50 years of age. Hazard ratio was 4.4 (95% CI: 2.1–9.5) for women with a history of cardiac disease compared with those without a history of cardiac disease. CONCLUSIONS. Cardiotoxicity of trastuzumab varies considerably across subgroups of patients. The long-term safety profile was less favorable than in the largest clinical trial. Strategies to reduce cardiotoxicity in high-risk women should be investigated.